Grain filling and fatty acid composition of safflower fertilized with integrated nitrogen fertilizer and biofertilizers - Seyed Sharifi, Raouf; Namvar, Ali; Seyed Sharifi, Reza (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effects of the integrated application of nitrogen fertilizer and biofertilizers on the yield, grain filling period, and composition of fatty acids of safflower (Carthamus tinctorius). Split-plot experiments were carried out during the 2011 and 2012 crop seasons. The treatments consisted of seed inoculation with plant growth-promoting rhizobacteria (Azotobacter chroococcum strain 5, Azospirillum lipoferum strain F, and Pseudomonas putida strain 186) in the subplots, including a control without seed inoculation; and of the application of N fertilizer at different rates (60, 120, and 180 kg ha-1 urea) in the main plots, including a control without N. The highest grain yield, grain filling period, and effective grain filling period were obtained by the application of 180 kg ha-1 urea and by seed inoculation with P. putida. The application of high N rates and P. putida inoculation resulted in 25.66% increase of the potential rate of grain filling. Biofertilizer inoculation in seed reduced the contents of saturated fatty acids (palmetic and stearic acids) and increased the contents of unsaturated fatty acids (linoleic, linolenic, and oleic acids). The suitable amount of N fertilizer (between 120 and 180 kg ha-1 urea) can improve plant growth, and the quantity and quality of oil in seeds treated with P. putida in safflower plants.